Prevention of Radiodermatitis With Topical Chinese Herbal Medicine: A Systematic Review and Meta-Analysis - Yu, Hui-Bo; Han, Bao-Jin; Cao, Hui-Juan (Frontiers in Pharmacology, 2022)
Objectives Topical Chinese herbal medicine (TCHM) is widely used to prevent radiodermatitis in patients who will receive radiation therapy in China. However, evidence regarding its efficacy remains limited. The purpose of the review is to evaluate the effects of TCHM in preventing of radiodermatitis. Methods Protocol of this review was registered in PROSPERO (CRD42020220620). Relevant clinical trials were identified (from January-1-2010 to September-26-2021) through 7 electronic databases. Quality of the included articles were assessed through Cochrane risk of bias tool. Primary outcomes of interest were the incidence of radiodermatitis and the grade of radiodermatitis according to RTOG (Radiation Therapy Oncology Group). Secondary outcomes included the recovery time of skin and mucosa, the occurrence time of radiodermatitis, the radiation dose, quality of life and, adverse events. Data was summarized using risk ratio (RR) calculations and 95% confidence intervals (CI) for binary outcomes or mean difference (MD) with 95% CI for continuous outcomes. Certainty of the evidence was assessed according to the GRADE criteria. Results 40 randomized clinical trials (RCT) were included in this review. Compared with routine drugs TCHM may have an advantage in reducing RTOG grading (RR=0.47, 95%CI 0.39 to 0.56), decreasing the recovery time of radiodermatitis (MD=-1.99 days, 95%CI -2.88 to -1.10 days), delaying the occurrence of radiodermatitis (MD=2.01, 95%CI 1.04 to 2.99) and improving the quality of life of patients (RR=1.46,95%CI 1.03 to 2.06). Compared with conventional therapy, TCHM may also have an advantage in decreasing the grade of RTOG (RR=0.31, 95%CI 0.20 to 0.47). Conclusions Current low evidence revealed that TCHM may have better efficacy in prevention of radiodermatitis; however, more high-quality RCTs are still warranted to testify this conclusion.